2000
DOI: 10.1523/jneurosci.20-01-00464.2000
|View full text |Cite
|
Sign up to set email alerts
|

Medial Frontal Cortex in Action Monitoring

Abstract: Effective behavior requires continuous action monitoring. Electrophysiological studies in both monkeys and humans have shown activity in the medial frontal cortex that reflects dynamic control and monitoring of behavioral acts. In humans, the centromedial frontal cortex shows an electrical response within 100 msec of an error, the error-related negativity (ERN). The ERN occurs only when subjects are aware of making an error, suggesting that a critical factor may be self-monitoring of the action process. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
236
5
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(278 citation statements)
references
References 36 publications
35
236
5
2
Order By: Relevance
“…Alternatively, the ERN conflict-detection model holds that the ERN merely reflects the degree of response conflict experienced by subjects (Cohen et al, 2000;Botvinik et al, 2001). This theory fits well with data showing ERNs or anterior cingulate activity for correct responses (Carter et al, 1998;Luu et al, 2000;Scheffers and Coles, 2000;Vidal et al, 2000) and responses showing a higher degree of motor conflict (Barch et al, 2000;Gehring and Fencsik, 2001;van Veen et al, 2001). As pointed out by Paus (2001), the ERN conflict-detection model emphasizes the "evaluative" nature of the anterior cingulate cortex.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Alternatively, the ERN conflict-detection model holds that the ERN merely reflects the degree of response conflict experienced by subjects (Cohen et al, 2000;Botvinik et al, 2001). This theory fits well with data showing ERNs or anterior cingulate activity for correct responses (Carter et al, 1998;Luu et al, 2000;Scheffers and Coles, 2000;Vidal et al, 2000) and responses showing a higher degree of motor conflict (Barch et al, 2000;Gehring and Fencsik, 2001;van Veen et al, 2001). As pointed out by Paus (2001), the ERN conflict-detection model emphasizes the "evaluative" nature of the anterior cingulate cortex.…”
supporting
confidence: 83%
“…This favors the interpretation that the internal error signal itself is unconscious and that the ERN is probably associated with the conscious perception of the errors. This view is supported by findings from Luu et al (2000), who found a linear increase in the amplitude of the ERN with increasingly late responses in a task defining late responses as errors.…”
Section: The Nature Of the Ern Componentmentioning
confidence: 56%
“…6A), we did not find any modulation of the neural activity following RTs as a function of speed, in none of the three conditions (slow hits, fast hits and errors). However, in a previous scalp-ERP study, the authors found larger errorrelated brain activity (ERN) for "late" (but still correct) responses, relative to fast (and correct) responses (see Luu et al, 2000). There are a number of methodological differences between the present experiment (using a Go-noGo task leading to a low variability in RTs, see also Fig.…”
Section: Left Dorsal Anterior Cingulate (Patient Sg)contrasting
confidence: 48%
“…Interestingly, Luu et al (2000) showed that the ERN can also be elicited in late responses. Luu and colleagues used a deadline reaction task in which participants were told to respond within a given time interval or the response will be considered late and scored as an error.…”
Section: Discussionmentioning
confidence: 99%